The supply side of the housing boom and bust of the 2000s - Andrew Haughwout; Richard W. Peach; John Sporn; Joseph Tracy (Federal Reserve Bank of New York, 2012)
The boom and subsequent bust in housing construction and prices over the 2000s is widely regarded as a principal contributor to the Financial Panic of 2007 and the subsequent Great Recession. As of this writing, housing market activity remains at depressed levels as the economy slowly resolves the legacy of excess supply and sharply lower prices. Over 2.6 million foreclosures have been completed since 2008 and 1.9 million foreclosures are in process. Much has been written about the demand side of this pronounced housing cycle, in particular, the innovations in mortgage finance and the loosening of underwriting standards that greatly expanded the pool of potential homebuyers. In this paper, we take a closer look at developments on the supply side of the housing market. Following a short literature review, we begin with a descriptive review of housing production, sales, and prices at the national, regional, and state levels. We then look at developments in the homebuilding industry over this period. We also take a closer look at land markets using a quarterly price index for metropolitan statistical areas with both elastic and inelastic housing supplies across the United States. An important question is to what extent the supply side of the market contributed to the boom/bust dynamics. A second question is whether the significant changes in the industrial organization of the homebuilding industry exacerbated or ameliorated this supply impact.
Keywords: R30; R14; D40; 330; housing supply; homebuilders